Health and religion : a study of health-seeking behaviour in Kayamandi, Western Cape in the context of "medical pluralism" - Gwele, Malibongwe P (Department of Religious Studies, 2014)
This small-scale study explores the concept of medical pluralism by looking at the health-seeking strategies of a selected group of residents in Stellenbosch's Kayamandi township. The study addresses the following three primary research questions: What are the health-seeking strategies of the target group? What factors significantly influence their health-seeking behaviour; and why are the respondents using more than one health-seeking strategy? We have used theoretical formulations derived from literature together with data we collected by questionnaires and interviews to respond to these questions. Our target group consisted of a mix of isiXhosa-speaking Christians, which fall into one of the following three groupings: Ecumenical, African Independent Zionists, and African Independent Non-Zionists. We applied a variety of methods to collect our data namely: survey questionnaire, in depth interviews and a focus group interview. Basic statistical and qualitative analysis techniques were used to analyze the data. We tested various potential variables before we concluded that Christian affiliation and gender are two major variables in this study that seem to influence our respondents' choices of strategy. The resulting data indicated that almost all of our respondents are mixing health seeking strategies. They are mixing in two ways: either in a complex way (multiple health seeking strategies for a single ailment), or a simple way (different strategies for different ailments). Even though Western Medicine is a dominant and the only legalized health-seeking strategy in South Africa this research suggests that there is a growing use of other health-seeking strategies, either alternatively or complementarily to Western Medicine. Reasons for this are discussed in this research report, and include firstly, conviction of experience and knowledge of health and illness among others. Secondly, we have established that these determinants transcend accessibility and availability of, particularly, Western medicine facilities. Respondents utilize three different health-seeking strategies selectively through 'border crossing' with minimal conflict.